Options to reform the European Union legislation on GMOs: post-authorization and beyond - Eriksson, Dennis; Custers, René; Edvardsson Björnberg, Karin; Hansson, Sven Ove; Purnhagen, Kai; Qaim, Matin; Romeis, Jörg; Schiemann, Joachim; Schleissing, Stephan; Tosun, Jale; Visser, Richard G. F. (Trends in biotechnology, 2020)
We discuss options to reform the EU genetically modified organism (GMO) regulatory framework, make risk assessment and decision-making more consistent with scientific principles, and lay the groundwork for international coherence. In this third of three articles, we focus on labeling and coexistence as well as discuss the political reality and potential ways forward.
Gesehen am 18.05.2020